In memory computation using quantum‐dot cellular automata. Issue 6 (18th September 2020) - Goswami, Mrinal; Pal, Jayanta; Roy Choudhury, Mayukh; Chougule, Pritam P.; Sen, Bibhash
Abstract : The conventional computing system has been facing enormous pressure to cope with the uprising demand for computing speed in today's world. In search of high‐speed computing in the nano‐scale era, it becomes the utmost necessity to explore a viable alternative to overcome the challenges of the physical limit of complementary‐metal‐oxide‐semiconductor (CMOS). Towards that direction, the processing‐in‐memory (PIM) is advancing its importance as it keeps the computation as adjacent as possible to memory. It promises to outperform the latencies of the conventional stored‐program concept by embedding storage and data computation in a single unit. On the other hand, the bit storing and processing capability of Akers array provides the foundation of PIM. Again, quantum‐dot cellular automata (QCA) emerges as a promising nanoelectronic to put back CMOS to give fast‐paced devices at the nanoelectronics era. This work presents a novel PIM concept, embedding Akers array in QCA to achieve high‐speed computing at the nano‐scale era. QCA implementation of universal logic utilizing Akers array signifies its processing power and puts forth its potentials. A universal function is considered for testing the effectiveness of the proposed PIM cell. The performance evaluation indicates the efficacy of QCA PIM over the conventional Von Neumann architecture.